1999
DOI: 10.1097/00000421-199912000-00002
|View full text |Cite
|
Sign up to set email alerts
|

Squamous Cell Carcinoma Antigen, Circulating Immune Complexes, and Immunoglobulins in Monitoring Squamous Cell Carcinoma of Head and Neck

Abstract: This study investigates the clinical utility of squamous cell carcinoma antigen (SCC-Ag), circulating immune complexes (CIC), and immunoglobulins (IgA, IgG, IgM) in the diagnosis, monitoring, and prognosis of 117 squamous cell carcinoma of the head and neck (SCC-HN) patients having local and/or systemic treatment. Serum marker levels were measured in a prospective study. SCC-Ag was positive in 28.2% of patients, the CIC in 63.2%, the IgA in 11.1%, the IgG in 15.4%, and the IgM in 9.44%. Statistically significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Moreover, another study presented data inconsistency was excluded . Eventually, eleven publications met the criteria for qualitative and quantitative syntheses in Figure …”
Section: Resultsmentioning
confidence: 99%
“…Moreover, another study presented data inconsistency was excluded . Eventually, eleven publications met the criteria for qualitative and quantitative syntheses in Figure …”
Section: Resultsmentioning
confidence: 99%
“…Presuming the involved antigens to be of malignancy-specific, serum CIC levels in cancer patients have been used for early diagnosis, metastatic spread, tumor burden, degree of aggressiveness, therapeutic response as well as prognosis. (9,13,15,16) Several factors become clear from the values given in Table 1. The mean levels of CIC in each category of patients differ significantly (p<0.001) from the mean level in the normal subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Observations in the present investigation are congruent with these reports. Although there are record on relationship of CIC levels to the stages of malignancies (15) no detailed study correlating CIC levels with histological grades has been reported so far. We had obtained significant correlation between CIC levels and histopathological grades of oral cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these assays have been developed for bacterial, viral or allergen antigens. In a few cases, detection of autoantigens as CIC has been proposed to enhance the sensitivity of cancer detection or prognosis monitoring utilizing prostate-specific antigen (PSA), 6 squamous cell carcinoma antigen, 7 carcinoembryonic antigen 8 and CA-125. 9 Thus, autoantigen-antibody complexes have been shown to be useful disease biomarkers, but progress in the discovery of new CICs has been extremely slow.…”
Section: Introductionmentioning
confidence: 99%